Variability of ground reaction force: Characteristics for slow running speeds - Smith, G. A.; Fewster, B. (Medicine & Science in Sports & Exercise, 1996)
Traditional studies of ground reaction forces in running have typically used overground running with a force plate for measuring a single stance phase. Complications associated with this approach include the difficulties of measuring successive steps, controlling running speed and "targeting" of the forceplate. Recently developed treadmills with force measuring instrumentation allow a more controlled collection of vertical ground reaction forces (VGRF) in gait. This study was part of a larger project dealing with walk-run transitions which made use of an instrumented treadmill system for measuring VGRF with a sampling frequency of 600 Hz. Nine subjects ran a series of five speeds from 1.6 to 2.4 m/s (in 0.2 m/s increments) as part of the larger data collection. Ten seconds of force data were collected at each speed allowing analysis of about ten consecutive strides. As expected, stride length increased from about 1.3 to 1.9 m while stride rate increased from 1.21 to 1.27 Hz in the speed range. Midstance VGRF also consistently increased with running speed (r = .97) from 1083 to 1314 N at 2.4 m/s. Stride-to-stride variability of about 40 to 50 N (mean of subject SD) was similar across speeds. These data, based on treadmill running with control of speed and with consecutive stride measurement capability, probably provide more accurate assessment of VGRF variability than do previous overground running studies.